2014
DOI: 10.1177/8755122514553987
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Proper Medication Inhaler Technique in Adult Patients

Abstract: Background: Many medications used to manage pulmonary disease are delivered via unique inhalation devices. Proper technique in using these devices is required for effective medication delivery. Objective: To assess the degree of proper inhaler technique among adult patients. Methods: Patients using inhalers were identified and then interviewed by pharmacy personnel regarding inhaler use. Checklists were used to document the adherence to manufacturers' directions for each respective inhaler, and data were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For studies that did not provide an overall error rate, [41][42][43] it was inferred based on the reported inhalation step with the highest frequency of error. For one study, 44 the overall device use error was considered the same as the reported error rate from the single inhalation step for which data were provided. That study also reported patients using Spiriva without specifying whether the medication was delivered via Respimat or Handihaler ® .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For studies that did not provide an overall error rate, [41][42][43] it was inferred based on the reported inhalation step with the highest frequency of error. For one study, 44 the overall device use error was considered the same as the reported error rate from the single inhalation step for which data were provided. That study also reported patients using Spiriva without specifying whether the medication was delivered via Respimat or Handihaler ® .…”
Section: Discussionmentioning
confidence: 99%
“…Among these articles, 33 did not provide information on device use errors, resulting in a total of 12 publications that were included in this meta-analysis. 22,[39][40][41][42][43][44][45][46][47][48][49] Since this study involved reviewing aggregate level secondary data published in publicly available studies and there was no access to primary patient-level data, protocol approval by the Institutional Review Board and Ethical Committee was waived.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…12 Lack of proper exhalation prior to inhalation was one among the three most common errors in 25% of the inhaler users. 23 Hence, a need to emphasize on this step for proper use of inhaler device is essential. Of 120 patients interviewed, only 60% adherent to asthma medications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Lack of proper exhalation prior to inhalation was one among the three most common errors in 25% of the inhaler users. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%